Визначення ставки дисконтування - Лілюк, Катерина Володимирівна (НТУ "ХПІ", 2015)
Розглядаються різні варіанти визначення ставки дисконтування і обґрунтовується вибір тієї чи іншої величини в якості найбільшприйнятною для оцінки вартості діючого підприємства. Розкрито суть ставки дисконтування для визначення вартості нематеріального активу у межах доходного підходу. Досліджено методику визначення середньозваженої вартості капіталу банку як базову ставку для знаходження ставки дисконтування при оцінці нематеріального активу. Проаналізовано додаткові премії за ризик та низьку ліквідність, які є обов’язковими елементами ставки дисконтування.

Offered various options for determining the discount rate and justifies the choice of a particular value as most appropriate for evaluating the value of the enterprise. Conclusions: an approach based on CAPM model evaluation of capital assets, is the most reasonable, if you have the required amount of data compared to joint-stock companies to go public and its shares are traded on the organized securities market; the cumulative method is more preferable case, and the lack of comparative data and in the evaluation of small and private companies; in cases when the stock market is not developed enough or the shares of the company do not turn on the market, and the company-the analog is hard to find, the calculation of the discount rate on the CAPM model can be complemented by model results of cumulative construction; given the trend of the stock market to decrease of profitability, it is necessary to consider expediency of application of not one but several levels of discount rates for each forecast year, and after the forecast period, is true even for developed countries.
Definition of discounting rates
Keywords: метод САРМ; ринкова ставка дохідності; кумулятивний метод; ставка прибутковості; ризик; низька ліквідність; CAPM method; discount rate; market rate of return; cumulative method; risk factors